(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Other than as decor, the Ramayana story-relief of Prambanan temple functions as teachings in visual form. The teachings source, a heroism narration of Rama (also called the Ramayana epic), is a holy book originally written by Valmiki, an Indian nationality, which later spread to various areas, including Java Island. Javanese society was known as open to external cultures. Conversely, they did not forthwith use it as their teachings. The epic later encountered a change in the form of story-part addition, written as Ramayana Jawa Kuno (RJK). Several researchers believe that RJK was employed as guidance in the making of Ramayana story-relief, as there is a conformity between the written text and the rendering sculptures. Thus, the RJK text was likewise employed by the author to analyze the depictions of each scene in the relief panels. Nevertheless, the analyses conversely found some differences in some scenes and objects, which show the presence of text interpretation and the discretion of the sculptures at the time.